The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.11591/ijai.v11.i1.pp161-172
|View full text |Cite
|
Sign up to set email alerts
|

Artificial speech detection using image-based features and random forest classifier

Abstract: The ASVspoof 2015 Challenge was one of the efforts of the research community in the field of speech processing to foster the development of generalized countermeasures against spoofing attacks. However, most countermeasures submitted to the ASVspoof 2015 Challenge failed to detect the S10 attack effectively, the only attack that was generated using the waveform concatenation approach. Hence, more informative features are needed to detect previously unseen spoofing attacks. This paper presents an approach that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Artificial speech detection techniques have witnessed significant evolution, falling into three primary categories: classic machine learning, end-to-end learning, and hybrid methodologies. Classic machine learning entails the manual crafting and extraction of predetermined features from data samples, which are then subject to separate classification modules [4,5]. In contrast, end-to-end learning orchestrates the automatic and joint identification and learning of all data sample features to determine their class labels.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial speech detection techniques have witnessed significant evolution, falling into three primary categories: classic machine learning, end-to-end learning, and hybrid methodologies. Classic machine learning entails the manual crafting and extraction of predetermined features from data samples, which are then subject to separate classification modules [4,5]. In contrast, end-to-end learning orchestrates the automatic and joint identification and learning of all data sample features to determine their class labels.…”
Section: Related Workmentioning
confidence: 99%
“…RF was considered in this evaluation due to its demonstrated strong performance in the ASVspoof 2015 challenge [4]. RF is an ensemble learning model that employs decision trees for classification and regression.…”
Section: Classifiersmentioning
confidence: 99%
“…Tan et al [19], showed a method for engineer image-based features when used with a RF classifier to identify artificial speech by use of data transformation techniques. The two goals are as follows: i) from the mel-frequency cepstral coefficients representation of the speech signal, extract image-based features; and ii) compare the effectiveness of using RF and the extracted features with the existing approaches to determine the authenticity of voices.…”
Section: Literature Surveymentioning
confidence: 99%